Telebasis rojinegra (Odonata: Zygoptera: Coenagrionidae) sp. nov. from Costa Rica - Haber, William A. (Zootaxa, 2020)
Telebasis rojinegra sp. nov. was recorded from ponds at La Selva Biological Station and three other sites in the Caribbean lowlands of Costa Rica. The new species appears closely related to T. boomsmae Garrison, 1994 recorded from Mexico, Belize and Costa Rica, T. collopistes Calvert, 1902 ranging from Mexico to Honduras, and T. garrisoni Bick & Bick, 1995 from South America, but differs in having straighter and more elongate paraprocts and a half black pattern on the rear of the head. The female mesostigmal plates are also distinct from the above species. Telebasis rojinegra was active on the water primarily during afternoon hours.